Studi kasus kepemimpinan kepala sekolah dalam menerapkan sekolah inklusi di SD Negeri 4 Truwolu Kecamatan Ngaringan Kabupaten Grobogan - Kartikawati, Eni; Utomo, Erry; Kanzunnudin, Moh.; Shokid, Wawan (Universitas Sarjanawiyata Tamansiswa, 2024)
This study aims to examine the role of the principal's leadership in implementing inclusive schools in SD Negeri 4 Truwolu, Ngaringan District, Grobogan Regency. The research method used is qualitative narrative with a case study approach. Data were collected through observations, in-depth interviews, and documentation studies. The results of the study show that school principals have an important role in implementing inclusive schools through policies and programs that support the admission of students with special needs. The principal facilitates teacher training, curriculum modification, and the provision of accessible infrastructure. In addition, principals build partnerships with parents and the community to create an inclusive learning environment. This study concludes that visionary, collaborative, and adaptive leadership of school principals is the key to success in implementing inclusive schools in SD Negeri 4 Truwolu.